IMPLEMENTATION OF BARCODES IN THE MOBILE-BASED OKESHOP MSME INVENTORY SYSTEM - Jayusman, Hadi; Mahardika, Fajar; Ratih, Ratih (STKIP PGRI Tulungagung, 2025)
Inventory can make it easier for workers to manage inventory. One of the business owners who uses the Inventory System is Okeey Shoop. The aim of this inventory system is to be able to unite the totality of related data. This unification was attempted for structured data collection and storage to make it more efficient. Barcodes enable MSMEs to accurately and quickly track their goods. By using a barcode scanner connected to a mobile application, the process of recording incoming and outgoing goods becomes more efficient, reducing human error and the time needed to manage stock. This data includes reporting on distribution and inventory of goods. The main benefit of this system is to reduce the number of errors in data collection and transactions. The method used is extreme programming where analysis, design, coding and testing are carried out. The results of the research found that this system functions well, speeds up employees in serving customers, and makes it easier for owners to monitor business activities and allocate funds appropriately to procure Okeey Shop needs.